HEAVY METAL ANALYSIS OF RAW KASEESA BY INDUCTIVELY COUPLED PLASMA (ICP) (International Journal of Ayurveda and Pharma Research, 2018)
Due to global recognition of Ayurveda formulations, the herbo mineral formulations of Ayurveda are questioned because of heavy metal contents found in many studies. Kaseesa (green vitriol) chemically known as ferrous sulphate which is a well known mineral used in various formulations as haematinic and emmenagogue was studied for standardization before making one of its formulation. Raw Kaseesa was analyzed for heavy metals using sophisticated method of Inductively Coupled plasma and was found that it contained metals lead and copper outside permissible limit of pharmacopeia norms.For this study various samples were collected and evaluated by the Rasashastra experts and later by Ayurvedic Pharmacopoeial methods. After the confirm identity, the samples were selected for the Heavy Metal Analysis. Inductively Coupled Plasma (ICP) method used for this study and results found in raw Kaseesa are Copper 7.2153 ppm, Lead 1288.0 ppm and Mercury, Arsenic, Cadmium were not detected. The authors recommend further study of Kaseesa after its Shodhana and other processes to study whether such heavy metal (Cadmium, Lead, Arsenic, Mercury and copper) contents are found in the finished product.